New reflections on hard X-ray photon-in/photon-out spectroscopy. Issue 30 (28th July 2020) - Lafuerza, Sara; Retegan, Marius; Detlefs, Blanka; Chatterjee, Ruchira; Yachandra, Vittal; Yano, Junko; Glatzel, Pieter
Abstract : The combination of X-ray absorption with X-ray emission spectroscopy requires careful consideration of the experimental protocol. The article discusses general aspects with examples for bio-catalysis and colloidal magnetic nanoparticles. Abstract : Analysis of the electronic structure and local coordination of an element is an important aspect in the study of the chemical and physical properties of materials. This is particularly relevant at the nanoscale where new phases of matter may emerge below a critical size. X-ray emission spectroscopy (XES) at synchrotron radiation sources and free electron lasers has enriched the field of X-ray spectroscopy. The spectroscopic techniques derived from the combination of X-ray absorption and emission spectroscopy (XAS–XES), such as resonant inelastic X-ray scattering (RIXS) and high energy resolution fluorescence detected (HERFD) XAS, are an ideal tool for the study of nanomaterials. New installations and beamline upgrades now often include wavelength dispersive instruments for the analysis of the emitted X-rays. With the growing use of XAS–XES, scientists are learning about the possibilities and pitfalls. We discuss some experimental aspects, assess the feasibility of measuring weak fluorescence lines in dilute, radiation sensitive samples, and present new experimental approaches for studying magnetic properties of colloidal nanoparticles directly in the liquid phase.